Komposisi dan Keragaman Jenis Bajakah di Resort Sebangau Hulu Taman Nasional Sebangau - Belinda Hastari; Robby Octavianus (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Sebangau National Park (TNS) is a conservation area for peatland ecosystems with biological natural resources including medicinal plants namely Bajakah. The aims of this study were to identify and measure the composition and diversity level of Bajakah in TNS. Results of this study are expected to be a data baseline for TNS’ management especially the conservation of Bajakah. Data was collected using the observation method on a 15 plots study with analysis on the parameters of the Important Value Index (IVI), Species Diversity, and Species Evenness. Results of study recorded 6 species of bajakah in TNS, namely Akar Kuning, Bajakah Dango, Bajakah Darak, Bajakah Lunuk, Kalalawit Merah, and Kalalawit Putih. Based on IVI, Kalalawit Merah (Uncaria sp) is the most dominating (134,792 %), Species Diversity Index 1,36, and Species Evenness Index 0.759.